TERPENOIDS AS SOURCE OF ANTI-INFLAMMATORY COMPOUNDS - Prakash, Ved (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Terpenoids accounts for the major class of secondary metabolites produced by plants. It shows defense activity against environmental stress and help to heal injuries. Medicinal plants are rich in monoterpenoids, diterpenoids, sesquiterpenes, triterpenes, tetraterpenes, and ceramide. A number of therapeutic applications such as antibacterial, antimicrobial, antitumor, anti-inflammatory activity have been identified. Terpenoids are compounds similar to terpenes derived from 5-carbon monomer isoprene units. The review puts and detail insight on different class of compounds isolated from natural source from 2000 to 2016 showing anti-inflammatory potential of pharmacologically interesting agent and their mechanism of action. Keywords: Anti-inflammatory, Mechanism of action, Natural source, Plant, Terpenoid, Bioactive compound.